Implementasi Metode Iterative Dichotomizer Tree (ID3) Untuk Diagnosis Penyakit Pada Tanaman Bawang Merah - Eric Aji Panji Kurniawan; Nurul Hidayat; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Early detection can minimize the risk of crop failure and can be the determinant of the strategic control efforts.The detection that existed so far is still done manually, and knowledge of disease and pest of onion plant still lacking . The number of plant disease pests of onion is also quite a lot and make enough trouble for farmer detect that attacks. The utilization of the expert system detection process becomes easier and faster. Farmer can detect pest and plant disease early and independently as well. On the research of this kind of disease pest that can be detected as many as five pests diseases using methods of Iterative dichotomezer 3 (ID3) with 23 input from users of symptoms. The method is used to analyze the data of pest and plant disease of onion crops where as the result of system accuracy test between the detection and the result of Iterative dichotomezer 3 (ID3) method calculation has the accuracy level of 80% which use 20 data training and 20 data test.